Modulation of brain dead induced inflammation by vagus nerve stimulation - Höger, Simone; Gasch, Claudia; Selhorst, Jochen Walter; Fontana, Johann; Birck, Rainer; Waldherr, Rüdiger; Beck, Grietje; Sticht, Carsten; Seelen, M. A; van Son, WJ; Leuvenink, H; Ploeg, R; et al. (American journal of transplantation, 2010)
Because the vagus nerve is implicated in control of in- flammation, we investigated if brain death (BD) causes impairment of the parasympathetic nervous system, thereby contributing to inflammation. BD was induced in rats. Anaesthetised ventilated rats (NBD) served as control. Heart rate variability (HRV) was asses-sed by ECG. The vagus nerve was electrically stimu-lated (BD STIM) during BD. Intestine, kidney, heart and liver were recovered after 6 hours. Affymetrix chip-analysis was performed on intestinal RNA. Quantita-tive PCR was performed on all organs. Serum was collected to assess TNFΑ concentrations. Renal trans-plantations were performed to address the influence of vagus nerve stimulation on graft outcome. HRV was significantly lower in BD animals. Vagus nerve stimu-lation inhibited the increase in serum TNFΑ concentra-tions and resulted in down-regulation of a multiplicity of pro-inflammatory genes in intestinal tissue. In renal tissue vagal stimulation significantly decreased the ex-pression of E-selectin, IL1Β and ITGA6. Renal function was significantly better in recipients that received a graft from a BD STIM donor. Our study demonstrates impairment of the parasympathetic nervous system during BD and inhibition of serum TNFΑ through vagal stimulation. Vagus nerve stimulation variably affected gene expression in donor organs and improved renal function in recipients.
Gesehen am 24.05.2023